Pengaruh Sistem Manajemen Mutu ISO 9001:2015 Terhadap Kinerja Guru di Sekolah Menengah Atas - Finda Nestria Jelita; Ary Ferdian (Universitas Pesantren Tinggi Darul 'Ulum, 2019)
Teacher had a massive role on producing quality human resource graduates. One of the methods to measure teacher performance is the grade of student’s national exam. In order to make teacher’s performance measured and the quality is guaranteed, therefore we need a method to control the quality one of which is quality management ISO 9001:2015. This research have a purpose to discover the level of quality management system ISO 9001:2015 in SMAN 3 Bandung, to discover the level of teacher performance in SMAN 3 Bandung, find the effect of quality management ISO 9001:2015 on teacher performance in SMAN 3 Bandung. The method that being used to collect the data is questionnaire distribution to all of the teacher at SMAN 3 Bandung in total of 70 people. The data analytic method that being used is descriptive analytic, simple linear regression analytic, and classic assumption test. The result of the data processing showed that teacher’s performance in SMAN 3 Bandung is very good and quality management ISO 9001:2015 is also very good therefore have a great effect in SMAN 3 Bandung.